Pyomyoma associated with bacteremia and puerperal pyrexia: A case report - Ming-Chu Kenix Choi; Li-Ching Chen; Chia-Chieh Lee; Ming-Song Tsai (Elsevier, 2023)
Objective: To report a case of pyomyoma, a serious complication of the uterine leiomyoma, in a postpartum woman. As the occurrence of pyomyoma in association with pregnancy is rather rare, a brief literature review of the condition in pregnant women is provided. Case report: A 41-year-old woman was found to have pyomyoma following persistent fever during the postpartum period of a first-time vaginal delivery. Her pregnancy course was complicated by preterm labor, for which the patient had received tocolysis since 30-week gestation. The pyomyoma was promptly removed by myomectomy on day-6 postpartum. Conclusion: Pyomyoma can occur in both pre- and post-menopausal women, and may even complicate pregnancies. Therefore, obstetricians and gynecologists should be wary of pyomyoma in postpartum women with histories of leiomyoma that present with sepsis of unknown focus that is refractory to standard antibiotics. Fertility may be preserved through timely diagnosis, followed by a prompt intervention.